Paternalismo estatal y desarrollo de la agricultura extensiva en Australia Occidental - Tonts, Matthew; Paül i Carril, Valerià (Ería, 2005)
RESUMEN Se estudia el papel del gobierno de Australia Occidental en la creación de un sector y una región de agricultura extensiva. La notable implicación gubernamental en el desarrollo agrario, aquí caracterizado como «paternalismo estatal», fue una característica fundamental de la política rural del período 1868-1929. El trabajo evalúa la racionalidad de esta política, sus éxitos y sus limitaciones, y analiza asimismo cómo esta política acabó por conformar la geografía agraria y el doblamiento de Australia Occidental. RÉSUMÉ Paternalisme de l’État et développement de l’agriculture extensive en Australie Occidentale.- On étudie le rôle du gouvernement de l’Australie Occidentale en la création d’un secteur et d’une région agricole extensive. La considérable implication gouvernementale dans le développement agricole, ici décrite comme «paternalisme de l’État», était une caractéristique fondamentale de la politique rurale de la période 1868- 1929. L’article considère la rationalité de ce type de politique, ses succès et ses carences, et analyse comment cette politique aboutit à conformer la géographie agraire et le peuplement de l’Australie Occidentale. ABSTRACT State Paternalism and Development of Extensive Agriculture in Western Australia.- This paper examines the role of the Western Australian Government in the creation of an extensive agricultural industry and region. Considerable government involvement in agricultural development, described here as «state paternalism», was a key characteristic of rural policy in the period between 1868 and 1929. The paper considers the rationality for this policy approach, its successes and failures, and analyses how it ultimately shaped the agricultural and settlement geography of Western Australia. Palabras clave / Mots clé / Key words Paternalismo estatal, gobierno, agricultura extensiva, desarrollo rural, Australia Occidental. Paternalisme de l’État, gouvernement, agriculture extensive, développement rural, Australie Occidentale. State paternalism, government, extensive agriculture, rural development, Western Australia.